Treatment of poststroke constipation with moxibustion: A case report. Issue 24 (June 2018) - Wen, Junmao; Zhuang, Zhenjie; Zhao, Minhong; Xie, Dongming; Xie, Bo; Zhuang, Lixing; Liang, Zheng; Wu, Wei; Xu, Hongwei
Abstract: Rationale: Moxibustion, an important therapeutic measure of TCM, can stimulate acupoints to unblock the meridians and collaterals, regulate the function of qi and blood, support health, and expel pathogens. So it could be an effective and safe for the treatment of constipation and improvement of the quality of life in poststroke patients with constipation. Patient concerns: He has a history of constipation, with the defecation of hard, bound stool every 2 to 3 days with the help of glycerin enema. Diagnoses: Constipation for >6 months; Cerebral infarction for 9 months; Type 2 diabetes for 3 years. Hypertension for approximately 1 month. Interventions: From the fifth day after admission, 5 rounds of moxibustion with moxa cones were administered at the bilateral ST25 and CV6 acupoints. Outcomes: The patient successfully defecated within 1hour. Subsequently, the patient could maintain daily unobstructed defecation with a normal total stool weight and moderate hardness. Lessons: Moxibustion is effective and safe for the treatment of constipation and improvement of the quality of life in post-stroke patients with constipation.